The short‐term incidence of hepatocellular carcinoma is not increased after hepatitis C treatment with direct‐acting antivirals: An ERCHIVES study. Issue 6 (19th April 2018) - Li, Darrick K.; Ren, Yanjie; Fierer, Daniel S.; Rutledge, Stephanie; Shaikh, Obaid S.; Lo Re, Vincent; Simon, Tracey; Abou‐Samra, Abdul‐Badi; Chung, Raymond T.; Butt, Adeel A.
Abstract : Recent studies have reported higher rates of hepatocellular carcinoma (HCC) in individuals treated with direct‐acting antivirals (DAAs). However, making definitive conclusions has been challenging because of the heterogeneous populations and methodologies of these reports. We investigated whether DAA use is associated with higher rates of incident HCC compared to treatment with interferon (IFN)‐based regimens. We performed a retrospective, population‐based cohort study using the Electronically Retrieved Cohort of HCV Infected Veterans (ERCHIVES) database. In a cohort of 17, 836 persons, sustained virological response (SVR) was achieved by 66.6% and 96.2% of the IFN and DAA groups, respectively. Among all treated persons, risk of HCC was not higher in the DAA group compared to the IFN group (hazard ratio, 1.07; 95% confidence interval, 0.55, 2.08). Among persons with cirrhosis who achieved SVR, neither the HCC incidence rate nor HCC‐free survival were significantly different in the DAA group compared to the IFN group (21.2 vs. 22.8 per 1, 000 person‐years; P = 0.78 and log‐rank P = 0.17, respectively). Untreated persons with cirrhosis had a significantly higher HCC incidence rate (45.3 per 1, 000 person‐years) compared to those treated with either IFN or DAAs ( P = 0.03). Both groups of treated persons had significantly lower probability of HCC development compared to untreated persons (log‐rank, P = 0.0004). Conclusion: DAA treatment is not associated with a higher risk of HCC in persons with cirrhosis with chronic HCV infection in the short term. Previously reported higher rates of HCC associated with DAA treatment may be explained by both the presence of relatively fewer baseline HCC risk factors in persons treated with IFN as well as selection bias, given that DAA regimens were used to treat persons at higher risk for developing HCC. (Hepatology 2018;67:2244‐2253).